1995
DOI: 10.1590/s0074-02761995000100016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of Bacillus thuringiensis toxins

Abstract: The selectivity of Bacillus thuringiensis toxins is determined both by the toxin structure and by factors inherent to the insect. These toxins contain distinct domains that appear to be functionally important in toxin binding to protein receptors in the midgut of susceptible insects, and the subsequent formation of a pore in the insect midgut epithelium. In this article features necessary for the insecticidal activity of these toxins are discussed. These include toxin structure, toxin processing in the insect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 0 publications
0
13
0
8
Order By: Relevance
“…The best characterized among them is the APN receptor (Pacheco et al, 2009, Rajagopal et al, 2003Gill et al, 1995;Gill, 1995;Knight et al, 1994;Sangadala et al, 1994) and the cadherin-like receptor (Jurat-Fuentes and Adang, 2006;Flanagan et al, 2005;Zhang et al, 2005;Hua et al, 2004;Tsuda et al, 2003;Hara et al, 2003;Gahan et al, 2001;Valaitis et al, 2001;Nagamatsu et al, 1998a,b;Vadlamudi et al, 1995) identified in lepidopterans. In nematodes, glycolipids are believed to be involved in Cry toxin interaction (Griffitts et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The best characterized among them is the APN receptor (Pacheco et al, 2009, Rajagopal et al, 2003Gill et al, 1995;Gill, 1995;Knight et al, 1994;Sangadala et al, 1994) and the cadherin-like receptor (Jurat-Fuentes and Adang, 2006;Flanagan et al, 2005;Zhang et al, 2005;Hua et al, 2004;Tsuda et al, 2003;Hara et al, 2003;Gahan et al, 2001;Valaitis et al, 2001;Nagamatsu et al, 1998a,b;Vadlamudi et al, 1995) identified in lepidopterans. In nematodes, glycolipids are believed to be involved in Cry toxin interaction (Griffitts et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They reasoned that the initial toxic event is the formation of a small hole in the plasma membrane, impermeable to intracellular macromolecules. As ions and water enter the cell, a further breakdown of the stretched plasma membrane will occur, allowing progressively larger molecules to leak out of the cell [5][6][7]12]. In other words, experiments on tissue culture cells in the field of entomology clarified that Cry proteins have a fairly general capacity to form large nonspecific pores under certain conditions, including high Cry protein concentrations, long incubation times and relatively low pHs [18].…”
Section: Discussionmentioning
confidence: 99%
“…When this crystal is ingested by target insects, it develops an insecticidal activity due to partial digestion of the protoxin inside the midgut of the insect [7,18]. The insecticidal proteins in the crystal form two different families, Cry and Cyt, which have been classified on the basis of amino acid identity into more than 30 Cry subgroups and two Cyt subgroups [3].…”
mentioning
confidence: 99%
“…The selectivity of Bt toxin is determined by toxin structure and other factors on the body of the target insects. The binding process of the toxin onto the receptor in the midgut can only be successful whenever they are compatible to each other (Gill, 1995).…”
Section: The Effect Of Bt Toxin Cry2ab2 On Spodoptera Lituramentioning
confidence: 99%